High temperature oxidation and erosion of candidate materials for particle receivers of concentrated solar power tower systems. (August 2019) - Galiullin, T.; Gobereit, B.; Naumenko, D.; Buck, R.; Amsbeck, L.; Neises-von Puttkamer, M.; Quadakkers, W.J.
Highlights: Performance of candidate materials for centrifugal particle receivers was evaluated. Exposures were conducted under combined erosion-oxidation conditions at 400–750 °C. Pronounced erosion of candidate materials was observed at higher temperatures. Co-base alloy MAR-M-509 hardened by carbides showed good resistance to erosion. Abstract: The centrifugal particle receiver is a novel concept proposed for concentrated solar power plants (CSP) to increase their operating temperature and efficiency. In this concept solar radiation is directly absorbed by a layer of ceramic particles held at the inner surface of a rotating cylindrical receiver by the centrifugal force. During operation, the hot ceramic particles (up to 1000 °C) move slowly along the receiver wall as well as other system components (e.g. tubes), which leads to their degradation through high-temperature oxidation and erosion. In the present study, a series of high temperature erosion-oxidation exposures was undertaken to experimentally evaluate performance of selected candidate metallic materials for centrifugal particle receivers. The exposures were conducted in a laboratory test facility consisting of a resistance heated furnace filled with ceramic particles, in which the specimen holder was rotated. Typical high temperature materials, such as martensitic, ferritic and austenitic stainless steels, Ni-base and Co-base alloys were investigated. The specimens were discontinuously exposed at 400–750 °C for up to 500 h and further characterized by scanning electron microscopy (SEM) and energy/wavelength dispersive x-ray spectroscopy (EDX/WDX).